2011
DOI: 10.4012/dmj.2010-093
|View full text |Cite
|
Sign up to set email alerts
|

A study of self-adhesive resin cements for bonding to silver-palladium-copper-gold alloy — Effect of including primer components in cement base

Abstract: This study investigated the efficacies of adhesive resin cements (Clearfil SA Luting, Maxcem, G-CEM, RelyX Unicem Clicker, Vitremer Paste) for bonding to Ag-Pd-Cu-Au alloy not surface-pretreated with metal primer. For control, Panavia F 2.0 -developed for use with a proprietary metal primer, Alloy Primer-was tested with and without metal primer application. Pairs of alloy disks (10.0 and 8.0 mm in diameters, 3.0 mm thickness) were air-abraded with alumina and bonded with one of the cements. Shear bond strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…The 10-methacryloxydecyl 6,8-dithiooctanoate (MDDT) monomer in the MLP and the disulfide-methacrylate in the MBP have cyclic disulfide groups, whereas the 6-(4-vinylbenzyl-n-propyl) amino 1,3,5-triazine-2,4-dithiol, dithione tautomer (VTD) in the ALP conditioner has thione groups on the terminal monomer structure. The effectiveness of the sulfur-based functional monomers for the bonding of noble metals has been reported 12,13,21,27) . Shear testing of the noble alloy bonded using the MBP conditioner with different composite luting materials showed a bonding strength of 16.5 MPa after thermocycling (37,500 cycles), similar to the bonding strength achieved using the ALP conditioner 20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 10-methacryloxydecyl 6,8-dithiooctanoate (MDDT) monomer in the MLP and the disulfide-methacrylate in the MBP have cyclic disulfide groups, whereas the 6-(4-vinylbenzyl-n-propyl) amino 1,3,5-triazine-2,4-dithiol, dithione tautomer (VTD) in the ALP conditioner has thione groups on the terminal monomer structure. The effectiveness of the sulfur-based functional monomers for the bonding of noble metals has been reported 12,13,21,27) . Shear testing of the noble alloy bonded using the MBP conditioner with different composite luting materials showed a bonding strength of 16.5 MPa after thermocycling (37,500 cycles), similar to the bonding strength achieved using the ALP conditioner 20) .…”
Section: Discussionmentioning
confidence: 99%
“…There have also been several improvements in the chemical compositions of monomers and initiators to enhance their clinical performance 25,26) . Although adhesive resin luting agents and resinmetal bonding systems have evolved, little information about their effects on adhesion to noble alloys used for prostheses is available 27,28) . The purpose of the study was to evaluate the effects of surface treatments on bonding between a gold alloy and composite adhesive luting agents.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the two glass ionomer cements tested in the current study showed comparable results and these fractured during bond strength test prevalently in adhesive mode, both at 24 h and after TC ageing; no significant difference between GC-GIC and PAN was observed after thermocycling. Conventional GIC cements are characterised by a week tensile strength, fracture resistance and by the absence of chemical bond with noble metal in alloys [81,82]. Conversely, the mechanical properties of resin-modified glass ionomer cements (RMGIC) are generally greater than those of a conventional GIC; the compressive strength of the RMGIC at 24 h after setting is lower than that observed in conventional resin-free GIC [83].…”
Section: Discussionmentioning
confidence: 99%
“…Примена паладијума у индустрији почела је 1919. године, при чему је паладијум до данас коришћен за производњу електричних контаката, 3,4 хемијских катализатора, 5 накита и сатова, 6,7 стоматолошких протеза, уметака и круница зуба, 8,9 хируршких инструмената и тест трака за одређивање шећера у крви. 10 У аутомобилској индустрији као каталитички конвертор користи се за смањење емисије штетних полутана као што су угљен моноксид, угљен водоник и оксиди азота, претварајући их у угљен диоксид, воду и азот.…”
Section: примена и значај једињења паладијумаunclassified